Respuesta :
Answer: 3
Step-by-step explanation:
- You can immediately notice that the sum consists of the sum of two infinitely decreasing geometric progressions
- [tex]\displaystyle \large \boldsymbol {} \underline1+\underline 2+\underline {\frac{1}{2}} -\frac{2}{3} +\underline {\frac{1}{4}} -\frac{2}{9} +\underline{\frac{1}{8}} -\frac{2}{27} + \ldots = \\\\\\ \underbrace{\bigg(1+2+\frac{1}{2} +\frac{1}{4} \ldots \bigg)}_{\rm \big S_2}-2 \underbrace{\bigg(\frac{1}{3}+\frac{1}{9} +\frac{1}{27} \ldots \bigg)}_{\big S_3}[/tex]
- The formula for an infinitely decreasing geometric progression:
- [tex]\displaystyle \large \boldsymbol { \rm S=\frac{b_1}{1-q} \ \ ; \ \ |q|<1}[/tex]
- Where :
- q -denominator
- b₁ -is the first member of the progression
- Then:
- Denote the sum of the numbers in the first bracket for S₂ ; and in the second bracket for S₃
- [tex]\displaystyle \large \boldsymbol {} \rm S_2=\frac{2}{1-\dfrac{1}{2} } =\frac{2}{\dfrac{1}{2} } =4 \\\\\\\ S_3=\frac{\dfrac{1}{3} }{1-\dfrac{1}{3} } = \dfrac{1}{\dfrac{3}{\dfrac{2}{3} } } =\frac{1}{2}[/tex]
- Substitute the values :
- [tex]\large \boldsymbol {} \rm S_2-2S_3=4- 2\cdot \dfrac{1}{2} =\boxed{3}[/tex]